Cope's Rule and Romer's theory: patterns of diversity and gigantism in eurypterids and Palaeozoic vertebrates - Lamsdell, James C. (The Royal Society, 2010)
Gigantism is widespread among Palaeozoic arthropods, yet causal mechanisms, particularly the role of (abiotic) environmental factors versus (biotic) competition, remain unknown. The eurypterids (Arthropoda: Chelicerata) include the largest arthropods; gigantic predatory pterygotids (Eurypterina) during the Siluro-Devonian and bizarre sweep-feeding hibbertopterids (Stylonurina) from the Carboniferous to end-Permian. Analysis of family-level originations and extinctions among eurypterids and Palaeozoic vertebrates show that the diversity of Eurypterina waned during the Devonian, while the Placodermi radiated, yet Stylonurina remained relatively unaffected; adopting a sweep-feeding strategy they maintained their large body size by avoiding competition, and persisted throughout the Late Palaeozoic while the predatory nektonic Eurypterina (including the giant pterygotids) declined during the Devonian, possibly out-competed by other predators including jawed vertebrates.